PENGGUNAAN MEDIA GRAFIK MEMBACA RITEM PADA PEMBELAJARAN MUSIK DI SMP 8 PADANG - Niko Ariando; Tulus Handra Kadir; Jagar Lumban Toruan (FBS Universitas Negeri Padang, 2012)
The purpose of this research is supposed to : Whether the use of the graphic media is an appropriate and effective to develop reading ability and play the rhythm on learning of the art by junior high school students 8 padang. This research is a kind of action research class II by performing actions. This research is focused to the students class VIIIc that cannot have the standard set KKM at school on learning student class VIIIc by using graphic media to make it easier to read and play the rhythm notation got success on the second cycle reachis 83,95% from 62,5% in the previous cycle. This learning strategies using graphic media to read and play rhythm notation mure helping the students in learning process plays outcomes arranger and sing national song.